Is the LysM domain of L. monocytogenes p60 protein suitable for engineering a protein with high peptidoglycan binding affinity?. Issue 6 (1st November 2016) - Yu, Minfeng; Yang, Jing; Guo, Minliang
ABSTRACT: Lysin motif (LysM) is a highly conserved carbohydrate binding module that is widely present in proteins from both prokaryotes and eukaryotes. LysM domains from many LysM-containing proteins can be taken out of their natural context and retain their ability to bind peptidoglycan. Therefore, LysM has enormous potential for applications in both industry and medicine. This potential has stimulated an intensive search for LysM modules with different evolutionary origins. The p60 protein (Lm-p60) is an NlpC/P60-containing peptidoglycan hydrolase secreted by Listeria monocytogenes . The N-terminus of Lm-p60 contains 2 LysM modules separated by an SH3 module. Our recent study of Lm-p60 demonstrates that the N-terminal half of Lm-p60, comprised of 2 LysM and 1 SH3 module, is able to recognize and bind peptidoglycan. The LysM domain of Lm-p60 contains only 2 LysM modules, which is the minimum number of LysM modules in most NlpC/P60-containing proteins, but it shows strong affinity for peptidoglycan. Moreover, these 2 LysM modules have only 38.64% similarity to each other. These data allowed us to conclude that the 2 LysM modules from Lm-p60 have different evolutionary origins, suggesting that they are suitable candidate peptidoglycan-binding modules for protein engineering in order to create a protein with a high binding affinity to peptidoglycan.